Theoretical modelling analysis on tensile properties of bioepoxy/clay nanocomposites using epoxidised soybean oils - Salam, H.; Dong, Roger (Hindawi Publishing Corporation, 2019)
A theoretical modelling framework was proposed to predict tensile moduli and tensile strengths of bioepoxy/clay nanocomposites in terms of clay content and epoxidised soybean oil (ESO) content, which could be influenced by properties of blended matrices in nanocomposites, clay filler type, orientation and dispersion status, clay morphological structures, and filler-matrix interfacial bonding. The random orientation of dispersed clay fillers played a significant role in predicting elastic moduli of bioepoxy/clay nanocomposites at clay contents of 1-8 wt% (ESO content: 20 wt%) according to Hui-Shia (H-S) laminate model and Halpin-Tsai (H-T) laminate model. In addition, when clay content was fixed at 5 wt%, H-S laminate model coincided well with the experimental data of bioepoxy/clay nanocomposites at the ESO contents of 0-40 wt%. Whereas, Hirsch model showed closer estimated values with experimental data at the ESO content of 60 wt%. Finally, Turcsányi-Pukànszky-Tüdõs (T-P-T) model predicted better tensile strengths of bioepoxy/clay nanocomposites at clay contents of 1-5 wt% (ESO content: 20 wt%) and at an ESO content of 20-60 wt% (clay content: 5 wt%).